Assessment of prophetic foods consumption among lactating mothers: Combining quantitative and qualitative approaches. - Abdul Basir, Siti Munirah; Mohd Shukri, Nor Azwani; Abdul Ghani, Radiah; Ibrahim, Muhammad; Khattak, Muhammad Muzaffar Ali Khan; Omar, Muhammad Nor (2018)
Introduction: The phrase ‘Prophetic food and medicine’ reflects the words and actions of the Holy Prophet Muhammad (PBUH) with the bearing of disease, treatment of disease, and care of patients. Among plants mentioned in the Al-Quran, Al-Hadith and Islamic literature are dates, pomegranates, figs, olive and black cumin seeds. These plants are widely used for medicinal purposes, as functional foods and industrial products. However, there are limited studies found regarding their effect on human milk quality and quantity. Thus, this paper aims to describe the methodology to assess knowledge, attitude, and practice of prophetic foods consumption among lactating mothers in Kuantan, Pahang. Methodology: Pregnant Malay mothers aged 18 to 40 years old, at a gestational duration of ≥ 32 weeks, are recruited. During the lactation period, their dietary intake (specifically the consumption of prophetic foods) are assessed using a quantitative method which is food frequency questionnaire. A subsample of these mothers is then interviewed using semi-structured interview method on the prophetic food consumption. Quantitative and qualitative data are analysed using SPSS and NVivo software, respectively. Result: Reports of positive effects of prophetic food consumption on lactation experience namely improving human milk production is anticipated from this study. In addition, it will provide a foundation for further exploration of the role of prophetic food consumption in the lactation process. Conclusion: This research is at the forefront to provide the data on potential practice and application of prophetic foods in positively influencing lactation experience and quality of human milk.